Интерактивные приёмы развития речевой культуры младших школьников - Шевченко, Г.В. (My University, 2016)
If creatively interpret and revise the curricula of the Russian language in the elementary school and the main focus has shifted to the development of oral language, the education of speech culture, a culture of verbal behavior of pupils in different situations, develop their ability to engage in dialogue and come up with a monologue to the audience will be more effective. One of the essential ways of solving the problem of speech development is the introduction in the educational process cycle lessons of rhetoric and speech culture. Thus, the rhetoric will provide the basis for bringing together different disciplines to build communication skills.
Keywords: speech culture; dialogue; rhetoric; communication skills